Experimentally Shock‐Induced Melt Veins in Basalt: Improving the Shock Classification of Eucrites. Issue 1 (10th January 2023) - Ono, Haruka; Kurosawa, Kosuke; Niihara, Takafumi; Mikouchi, Takashi; Tomioka, Naotaka; Isa, Junko; Kagi, Hiroyuki; Matsuzaki, Takuya; Sakuma, Hiroshi; Genda, Hidenori; Sakaiya, Tatsuhiro; Kondo, Tadashi; et al.
Abstract: Basaltic rocks occur widely on the terrestrial planets and differentiated asteroids, including the asteroid 4 Vesta. We conducted a shock recovery experiment with decaying compressive pulses on a terrestrial basalt at the Chiba Institute of Technology, Japan. The sample recorded a range of pressures, and shock physics modeling was conducted to add a pressure scale to the observed shock features. The shocked sample was examined by optical and electron microscopy, electron back‐scattered diffractometry, and Raman spectroscopy. We found that localized melting occurs at a lower pressure (∼10 GPa) than previously thought (>20 GPa). The shocked basalt near the epicenter represents "shock degree C" of a recently proposed classification scheme for basaltic eucrites and, as such, our results provide a pressure scale for the classification scheme. Finally, we estimated the total fraction of the basaltic eucrites classified as shock degree C to be ∼15% by assuming the impact velocity distribution onto Vesta. Plain Language Summary: Basaltic rocks occur on numerous planetary bodies, including Mars, the Moon, and the asteroid Vesta. Shock metamorphic features in meteorites from such bodies are the ancient imprints of past impact events. We can extract information about the bombardment histories experienced by such bodies if we have an accurate method to link the degree of metamorphism to the impact conditions. Although two such methods for basaltic rocks have been published, one of these does not have a scale that relates the shock features and peak pressures. In this study, we designed an impact experiment with a terrestrial basalt sample to add a pressure scale to one of these methods. We found that basaltic materials are more easily melted than previously expected. The shock features of our shocked sample match "shock degree C." The required pressure for producing the materials classified into this shock degree is 1–2 × 10 5 times greater than atmospheric pressure. Our results may provide insights into impact processes on Vesta. We estimate that the total fraction of meteorites from Vesta classified into shock degree C is ∼15%. Key Points: We investigated the shock effects in basaltic rocks with impact experiments and shock physics modeling We added a pressure scale to the shock degree classification for basaltic eucrites, allowing us to link our results with the Stöffler table Localized melting occurs from 10 GPa rather than 20 GPa as previously thought